A Positive Association between T. gondii Seropositivity and Obesity - Reeves, Gloria M.; Postolache, Teodor T.; Mazaheri, Sara; Snitker, Soren; Langenberg, Patricia; Giegling, Ina; Hartmann, Annette; Konte, Bettina; Friedl, Marion; Okusaga, Olaoluwa; Groer, Maureen; Mangee, Harald; et al. (Frontiers in Public Health, 2013)
Obesity is a global public health problem that is linked with morbidity, mortality, and functional limitations and has limited options for sustained interventions. Novel targets for prevention and intervention require further research into the pathogenesis of obesity. Consistently, elevated markers of inflammation have been reported in association with obesity, but their causes and consequences are not well understood. An emerging field of research has investigated the association of infections and environmental pathogens with obesity, potential causes of low grade inflammation that may mediate obesity risk. In this study, we estimate the possible association between Toxoplasma gondii (T. gondii) infection and obesity in a sample of 999 psychiatrically healthy adults. Individuals with psychiatric conditions, including personality disorders, were excluded because of the association between positive serology to T. gondii and various forms of serious mental illness that have a strong association with obesity. In our sample, individuals with positive T. gondii serology had twice the odds of being obese compared to seronegative individuals (p = 0.01). Further, individuals who were obese had significant higher T. gondii IgG titers compared to individuals who were non-obese. Latent T. gondii infection is very common worldwide, so potential public health interventions related to this parasite can have a high impact on associated health concerns.